2014
DOI: 10.3892/ijmm.2014.1962
|View full text |Cite
|
Sign up to set email alerts
|

Duhuo Jisheng decoction treatment inhibits the sodium nitroprussiate-induced apoptosis of chondrocytes through the mitochondrial-dependent signaling pathway

Abstract: Chondrocyte apoptosis activated by the mitochondrial-dependent signaling pathway plays a crucial role in the cartilage degeneration of osteoarthritis. Duhuo Jisheng decoction (DHJSD), a herbal formula from traditional Chinese medicine, has been widely used for treating osteoarthritis (OA). However, the molecular mechanisms behind the therapeutic effect of DHJSD remain to be elucidated. In the present study, the effects of DHJSD on the mitochondrial-dependent signaling pathway in sodium nitroprussiate (SNP)-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The isolated cells were collected every 2 h and the chondrocytes were cultured in 50 ml culture flasks in 4 ml DMEM containing 10% FBS at 37°C and 5% CO 2 . The culture media were changed every 2 days and the cells were subcultured at 90% confluency (17). Collagen Type II Immunohistochemical Staining was performed to confirm the identity of the chondrocytes (data not shown), as previously described from our team (3,17).…”
Section: Methodsmentioning
confidence: 99%
“…The isolated cells were collected every 2 h and the chondrocytes were cultured in 50 ml culture flasks in 4 ml DMEM containing 10% FBS at 37°C and 5% CO 2 . The culture media were changed every 2 days and the cells were subcultured at 90% confluency (17). Collagen Type II Immunohistochemical Staining was performed to confirm the identity of the chondrocytes (data not shown), as previously described from our team (3,17).…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 7, DHJSD has an overall effect to eliminate "fenghan-shi", respectively, and thus to relieve pain of "Bi Zheng" through promoting "Gan" and "Shen" function and therefore strengthen the bones and tendons [30] . It also improves circulation and remove stasis of "Qi" and "Xue", reduces tissue swelling and relieves pain [20,22,23,26,32,39,40] . Some pharmacological studies have demonstrated that DHJSD may have effects of analgesia, immune function regulation, blood vessel dilation, anti-inflammation, and antiplatelet aggregation [20,22,23,26,32,39,40] .…”
Section: Discussionmentioning
confidence: 99%
“…It also improves circulation and remove stasis of "Qi" and "Xue", reduces tissue swelling and relieves pain [20,22,23,26,32,39,40] . Some pharmacological studies have demonstrated that DHJSD may have effects of analgesia, immune function regulation, blood vessel dilation, anti-inflammation, and antiplatelet aggregation [20,22,23,26,32,39,40] . In a study of the aging-related osteoarthritis, another common bone degenerative disease, Chen et al found that DHJSD may inhibit VEGF and HIF-1α to retard cartilage degradation in a rabbit model of osteoarthritis [53] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have proven that DHJSD has potential cooperation and polypharmacology against OA, and could inhibit chondrocyte apoptosis by the mitochondria-dependent signaling pathway (16). However, the mechanisms of how DHJSD inhibit the chondrocyte apoptosis by ER stress remain to be elucidated, which has limited its wider use.…”
Section: Introductionmentioning
confidence: 97%